Perceived Value Similarity With Important Others: Well-Being Implications for Emerging Adults - Belic, Jelisaveta; Boehnke, Mandy; Boehnke, Klaus (Frontiers in Psychology, 2022)
Emerging adults establish, question, and re-establish their values within most diverse social con-texts. Every social context privileges expressing certain values and/or punishes expressing con-flicting ones. This makes similarity between own values and values preferred in one’s life contexts psychologically desirable (person-environment fit). The present study focuses on the similarity of individuals’ values with the perceived values of important others from five immediate social contexts: family, friends, intimate partner, study group, and work group, and its relationship with life satisfaction. The sample consists of emerging adults from Serbia interacting with the five mentioned contexts (N=479). A mobile app with a game-like survey was launched to collect the data. The data indicate a positive association between life satisfaction and perceived value similarity with one’s family and with one’s intimate partner. Value similarity with their friends, study and work colleagues emerged as insignificant. Identity centrality and general importance of the immediate social contexts were studied as possible moderators. Identity centrality showed no moderation effect whereas general importance of the intimate partner did: High importance of the intimate partner decreased the positive effect of value similarity on well-being.